The impact of self-perceived burden, caregiver burden, and dyadic coping on negative emotions in colorectal cancer patient-spousal caregiver dyads: a dyadic analysis - Chen, Xuan; Wang, Zhiming; Zhou, Junrui; Lin, Chunyan; Luo, Huamin; Zhao, Jie; Loke, Alice Yuen; Li, Qiuping (Frontiers in Psychology, 2023)
Objective To explore the correlation between dyadic coping, self-perceived burden, caregiver burden, and anxiety/depression in colorectal cancer patient-spousal caregiver dyads. Methods This study surveyed 200 colorectal cancer patient-spousal caregiver dyads from August 2022 to December 2022. It evaluated self-perceived burden (only for patients), caregiver burden (only for spousal caregivers), dyadic coping, anxiety, and depression. It analyzed data through Pearson’s correlation and the actor–partner interdependence mediation model. Results Self-perceived burden and caregiver burden were significantly associated with the anxiety/depression of both individuals in colorectal cancer patient-spousal caregiver dyads; patients’ dyadic coping was associated with self-perceived burden and caregiver burden; caregivers’ dyadic coping was only associated with patients’ dyadic coping and depression. There was an actor–partner mediating effect of self-perceived burden between dyadic coping and anxiety/depression, but there was only a partner-mediating effect of caregiver burden between dyadic coping and anxiety/depression. Conclusion This study confirmed the interrelationship between self-perceived burden, caregiver burden, dyadic coping, anxiety, and depression. Self-perceived burden and caregiver burden mediated the relationship between dyadic coping and anxiety/depression in colorectal cancer patient-spousal caregiver dyads. This suggests dynamic interventions for self-perceived burden and caregiver burden can be implemented to improve anxiety/depression in both partners based on maintaining healthy dyadic coping between colorectal cancer patient-spousal caregiver dyads.